Cosmological observational constraints on the power law f(Q) type modified gravity theory - Sanjay Mandal; Sneha Pradhan; P. K. Sahoo; Tiberiu Harko (European Physical Journal C: Particles and Fields, 2023)
Abstract In modern cosmology, the curiosity of ultimately understanding the nature of the dark energy controlling the recent acceleration of the Universe motivates us to explore its properties by using some novel approaches. In this work, to explore the properties of dark energy we adopt the modified f(Q) gravity theory, where the non-metricity scalar Q, emerging from Weyl geometry, plays the dynamical role. For the function f(Q) we adopt the functional form $$f(Q)=Q+ 6γ \,H_0^2(Q/Q_0)^n$$ f ( Q ) = Q + 6 γ H 0 2 ( Q / Q 0 ) n , where $$n,\, γ ,\, H_0$$ n , γ , H 0 and $$Q_0$$ Q 0 are constants. Then, we test our constructed model against the various observational datasets, such as the Hubble, and the Pantheon+SHOES samples, and their combined sample, through the Markov Chain Monte Carlo (MCMC) statistical analysis. We also employ the parameter estimation technique to constrain the free parameters of the model. In addition, we use the constrained values of the model parameters to explore a few implications of the cosmological model. A detailed comparison of the predictions of our model with the $$Λ $$ Λ CDM model is also performed. In particular, we discuss in detail some cosmographic parameters, like the deceleration, the jerk, and the snap parameters, as well as the behavior of the dark energy and matter energy densities to see the evolution of various energy/matter profiles. The Om diagnostics is also presented to test the dark energy nature of our model, as compared to the standard $$Λ $$ Λ CDM paradigm. Our findings show that the considered version of the non-metric f(Q) type modified gravity theory, despite some differences with respect to the $$Λ $$ Λ CDM paradigm, can still explain the current observational results on the cosmological parameters, and provide a convincing and consistent account for the accelerating expansion of the Universe.